Anterior uveal melanoma in a blue-fronted Amazon parrot (Amazona aestiva) - Case report - Filho, Orlando Baptista de Camargo (2017)
ABSTRACT. de Camargo Filho O.B., Nemer V.C., Sanches A.W.D., Voltarelli- -Pachaly E.M., Santos A.L.Q., Germano R.M., Montiani-Ferreira F. & Pachaly J.R. [Anterior uveal melanoma in a blue-fronted Amazon parrot (Amazona aestiva) - Case report.] Melanoma de úvea anterior em papagaio-verdadeiro (Amazona aestiva) - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(Supl.1):127-130, 2016. Programa de Pós-Graduação em Ciência Animal, Universidade Paranaense, Campus Umuarama, Praça Mascarenhas de Moraes, 4282, Zona III, Umuarama, PR 87502-210, Brasil. Email: pachaly@uol.com.br A non-sexed 20-year-old blue-fronted Amazon parrot (Amazona aestiva) legally kept as a pet was examined with the chief complaint of a dark sclerocorneal eye lesion growing for at least a year without any medical attention. Clinical suspicion of a melanocytic tumor lead to surgery and the affected eye globe was enucleated. The eye was routinely processed for histopathology and stained with Hematoxilin and Eosin. Under light microscopy the ocular tissue sample showed a proliferation of pleomorphic melanocitic cells, the mitotic index was six mitotic figures per high power field, and the diagnosis was anterior uveal melanoma with choroidal extension but also with invasion of the sclera. The morphological diagnosis was anterior uveal melanoma, a rarely reported neoplasm in psittacine birds. Surgical treatment was successful and is the better indication in these cases.